Evaluation of the reliability of periapical radiographs in determining working length in the context of endodontic treatment - الدرويش مرح; ميسم خدام (Latakia University Journal -Medical Sciences Series, 2024)
Aim: This research aims to evaluate the reliability of periapical radiographs in determining the working length of the root canal in the context of endodontic treatment Materials and Methods: This study was designed as a laboratory radiological study. The research sample included 40 single-canal teeth with complete apex. The true working length was determined by inserting a file until it was seen from the apex with a magnifying glass at 2.5 magnification. Then, to take radiographs, the teeth were placed in a wax tray and the apical images of each tooth were taken. Limit after inserting the coolant until the top of the coolant is seen at the root apex Results: It was observed that there were statistically significant differences in the average measurements between the periapical radiography and the actual length, as this method gave a higher average, and its average was 1.25% higher than the average true length of the root canal. Conclusions: The study concluded that the reliability of periapical radiography in determining the working length is poor and the need to combine it with another method to determine the working length more accurately in the context of endodontic treatment.